Penerapan Pendekatan Scientific dan Model Problem Based Learning (Pbl) untuk Meningkatkan Hasil Belajar Biologi Materi Sel - Devi Putri Ardiyani; Rita Retnowati; Triasianingrum Afrikani (FKIP UNIVERSITAS PAKUAN, 2015)
The research is a Classroom Action Research with the subject of 38 students of class XI IPA 4. The research is aimed at improving the learning outcome of biology subject with the implementation of scientific approach and Problem Based Learning (PBL) model. The research was conducted in two cycles. There were 4 steps in a cycle: planning, doing, observing, and reflecting. There was an evaluation after each cycle by using an instrument that had been validated and tested for its reliability and its difficulty level. The research result shows the scientific approach and Problem Based Learning (PBL) model can improve the learning outcome of biology subject. It can be seen from the average score of class XI IPA 4 which is 65,3 or 41% from 39 students. In the first cycle, it became 74,4 or about 61%. The average score improved in the second cycle into 86,2 with the completeness of 84% from 38 students. Besides cognitive, the learning outcome was also measured from affective and psychomotor sides. The research result shows that the average score of students’ affective in cycle I is 74,2 and cycle II is 84,2 while the average score of psychomotor aspect in cycle I is 74,3 and improved in cycle II into 80,4. Based on the result achieved, it can be inferred that the effort of improving the learning outcome of biology subject at the class of XI IPA 4 of SMA Negeri 10 Bogor using Scientific approach and Problem Based Learning (PBL) model is successful.